Analysis of the Application of the Teams Games Tournament (TGT) Learning Model in Primary School - Galuh Ningtiaz, Putri; Alfan, Muhammad; Kuncoro, Tri (KnE Social Sciences, 2023)
Learning is a process of interaction that occurs between teachers and students, there are goals set by the teachers based on the conditions of students and schools. Learning objectives are activities to be achieved by students. One of the things that can affect student’s success in the learning process is the selection of learning models. In order to get optimal learning outcomes, the quality of learning must be improved. Quality improvement can start with the use of approaches, methods, models, and other activities that encourage students to be active participants in the learning process. Cooperative learning can support the problems that occur because there are activities that require cooperation. Cooperative learning has many types, one of which is the Teams Games Tournament (TGT). Several studies have discussed the use of the TGT type of learning model and have proven to be able to solve some of the problems that occur. The purpose of this paper is to review several articles that have been selected and then grouped based on the similarities that exist between them. In addition, this writing is done to find out what causes the need to use the TGT model in learning. Keywords: TGT, result of learning, student activity